Reactive Oxygen Species‐Scavenging Scaffold with Rapamycin for Treatment of Intervertebral Disk Degeneration. Issue 3 (10th December 2019) - Bai, Jinyu; Zhang, Yingzi; Fan, Qin; Xu, Jialu; Shan, Huajian; Gao, Xiang; Ma, Qingle; Sheng, Lei; Zheng, Xin; Cheng, Weinan; Li, Dazhuang; Zhang, Mingchao; et al.
Abstract: The chronic inflammatory microenvironment is characterized by the elevated level of reactive oxygen species (ROS). Here, it is hypothesized that developing an ROS‐scavenging scaffold loaded with rapamycin (Rapa@Gel) may offer a new strategy for modulating the local inflammatory microenvironment to improve intervertebral disk tissue regeneration. The therapeutic scaffold consisting of ROS‐degradable hydrogel can be injected into the injured degeneration site of intervertebral disk (IVD) and can release therapeutics in a programmed manner. The ROS scavenged by scaffold reduces the inflammatory responses. It is found that when rats are treated with Rapa@Gel, this results in an increase in the percentage of M2‐like macrophages and a decrease in M1‐like macrophages in the inflammatory environment, respectively. Regeneration of IVD is achieved by Rapa@Gel local treatment, due to the increased M2 macrophages and reduced inflammation. This strategy may be extended to the treatment of many other inflammatory diseases. Abstract : A reactive oxygen species‐scavenging scaffold loaded with rapamycin (Rapa@Gel) offers a new strategy for modulating the local inflammatory microenvironment to improve intervertebral disk tissue regeneration.